The Voice of Teachers about School and the Teaching Profession in Guinea-Bissau - Filipe Dias; Maria José Rodrigues (MDPI AG, 2023)
Teachers' view of the school is determinant for their action and condition of their activity and their professional development. This study focuses on the voice of teachers at community management schools in Guinea-Bissau in order to know the vision they have of the school and the teaching profession. For data collection, a personal and professional characterization questionnaire and interviews with thirty elementary school teachers were used. The results show that teachers value continuing education as a tool that allows them to perform the profession better. They identified some constraints related to the difficulty in the Portuguese language, the lack of didactic materials and teachers, isolation, and lack of community participation. Teachers refer to the school as a place of transmission of knowledge and values, highlighting the school as the key to development. According to teachers, the need for more infrastructure and materials as well as the greater involvement and commitment of the educational community are the main factors that must be improved. To conclude, we highlight the role that teacher training plays in the quality of their work and the efforts necessary for schools to respond to the needs of society.